2021
DOI: 10.3390/vaccines9060638
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Acceptance of COVID-19 Vaccination among Undergraduate Students from Central and Southern Italy

Abstract: At the end of 2020, the Italian Ministry of Health launched a national vaccination campaign to counteract the COVID-19 pandemic. The present study aimed at appraising levels of knowledge about and acceptance of COVID-19 vaccination in a sample of Italian undergraduates during the first phase of the immunization plan. A web-based questionnaire was administered to students attending universities in Bari, Naples, and Rome during the period February–April 2021. Of the total of 3226 participants, 91.9% were keen to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
121
6
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(153 citation statements)
references
References 26 publications
18
121
6
8
Order By: Relevance
“…[20][21][22] Results of a community-based study involving Italian undergraduate students reported a good level of knowledge and acceptance of COVID-19 vaccination, revealing a sufficient flow of information or an efficient communication campaign among this population. 23 This supports an imperative role of the media campaign and public health communications in combating the pandemic via behavioural change 24 and targeting a barrier to vaccine uptake. 25 The previous study was confined to a single or a few countries.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…[20][21][22] Results of a community-based study involving Italian undergraduate students reported a good level of knowledge and acceptance of COVID-19 vaccination, revealing a sufficient flow of information or an efficient communication campaign among this population. 23 This supports an imperative role of the media campaign and public health communications in combating the pandemic via behavioural change 24 and targeting a barrier to vaccine uptake. 25 The previous study was confined to a single or a few countries.…”
Section: Introductionmentioning
confidence: 74%
“…As per the tool, all queries were filled with "yes", "no" or "cannot determine" and "not applicable" and "not reported". 23 Accordingly, 15 articles were good, 13,24-37 6 were fair, 31,[38][39][40][41][42] and 3 were poor. [47][48][49]…”
Section: Methodology Quality Assessmentmentioning
confidence: 99%
“…In a UK survey, willingness to undergo COVID-19 vaccination was significantly associated with willingness to receive a 2020/21 IV [34]. Analogously, among Italian undergraduates, previous IV was associated with greater acceptance of COVID-19 vaccination (aOR 3.81; 95% CI: 1.18-12.27) [35]. Finally, a meta-analysis of four studies showed that previous IV was a strong predictor (OR 3.17; 95% CI: 1.84-5.46) of COVID-19 vaccine acceptance [36].…”
Section: Discussionmentioning
confidence: 91%
“…These high proportions demonstrate that people in most countries, on the whole, have accepted the need for vaccines and are eager to get vaccinated [ 3 , 4 ]. However, there remain some individuals who are reluctant to take the vaccine.…”
Section: Introductionmentioning
confidence: 99%